Climate change in the Carpathian forests: recent developments - Kholiavchuk, D; Mayr, S; Gurgiser, W. (7th Forum Carpaticum Conference. Carpathian Futures – Critical Transitions, 2023)
The review study presents the effects of climate change on Carpathian forests based on a literature search in the Web of Science and Scopus databases, resulting in 276 relevant papers. Climate warming (in combination with land-use changes) are considered to cause various responses of forests, such as an extension of the vegetation period, changes in wood production, shifts of treelines, bark beetle calamities or limitations in tree water relations. These responses may interfere, as e.g., rising temperatures lead to an earlier bud break and the prolonged vegetation favours wood production upslope. Also, changes in precipitation patterns and extreme droughts affect trees directly, whereas stressed trees are also more vulnerable to biotic attacks (e.g., bark beetles, fungi). Among the Carpathian forest species, Norway spruce is highly susceptible to climate change. It exhibited increased variability in radial growth in many areas, and heatwaves and droughts were found to substantially reduce growth rates. Fir species are overall less susceptible than spruce, but different lineages demonstrate varying responses. Beech forests are more affected by drought than heat, with decreasing summer precipitation posing a challenge in low-mountain regions. Oaks exhibit high adaptability, but severe and prolonged droughts make them susceptible to fungal attacks
Keywords: climate change, Carpathian forests, vegetation period, tree water relations, species-specific responses